INTERPRETING FEMALE ROLES IN THE “TAMING OF THE SHREW” (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the multifaceted portrayals of female characters in William Shakespeare's The Taming of the Shrew, moving beyond simplistic interpretations of their roles. Focusing primarily on Katherine Minola and Bianca Minola, the study analyzes their individual trajectories, their interactions within the patriarchal societal structure of Padua, and the various ways they assert agency or comply with societal expectations. By exploring their dialogue, actions, and reactions to male characters, this analysis uncovers the complexities of female identity, power dynamics, and the institution of marriage as depicted in the play.
Keywords: The Taming of the Shrew, Female Characters, Katherine Minola, Bianca Minola, Shakespeare, Gender Roles, Patriarchy, Agency, Early Modern Drama, Marriage